2009
DOI: 10.1017/s002966510900127x
|View full text |Cite
|
Sign up to set email alerts
|

Symposium 9: Competent to care A train-the-trainer method of teaching as a way of implementing the correct use of the ‘Malnutrition Universal Screening Tool’ in Norfolk: is it effective?

Abstract: Malnutrition is frequently undetected in care homes. It is recommended that residents are screened on admission and at suitable intervals thereafter. It is aimed to implement the 'Malnutrition Universal Screening Tool' ('MUST') in all care homes in Norfolk in order to fulfil this recommendation. Following a pilot of successful (but time-consuming) 'MUST' training a train-the-trainer package was developed as a practical way of achieving this goal. Courses were held in 2007, each comprising a study day and an as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 3 publications
(4 reference statements)
0
18
0
Order By: Relevance
“…The high turnover of staff suggests that frequent and repeated education programmes are required to maintain high levels of nutritional knowledge, which has considerable implications for manpower planning for community dietetics services as the providers of such training. Recently, the use of a ‘train‐the‐trainer’ method for educating nursing home staff in the use of ‘MUST’ was reported as successful (Lee & Scott, 2009); this may offer a possible solution to training needs in the nursing home setting.…”
Section: Discussionmentioning
confidence: 99%
“…The high turnover of staff suggests that frequent and repeated education programmes are required to maintain high levels of nutritional knowledge, which has considerable implications for manpower planning for community dietetics services as the providers of such training. Recently, the use of a ‘train‐the‐trainer’ method for educating nursing home staff in the use of ‘MUST’ was reported as successful (Lee & Scott, 2009); this may offer a possible solution to training needs in the nursing home setting.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing FoU's impact (Table 10, Fig. 6) on undernutrition is limited because other UK studies using "MUST" [17,51,85,87] did not report on prevalence change; and foreign studies [61,68,69,[88][89][90][91] used alternative outcomes or non-comparable nutritional screening tools (NST). Similar studies [83,92] implementing education and care pathways identified both a reduction [92] and no impact [83] in prevalence.…”
Section: Undernutrition Prevalencementioning
confidence: 99%
“…3,4,14 Research and the Cascade Model. 16,17 The literature is dominated by descriptions of how the cascade model has been applied 3,7,9,10,[12][13][14]18 and tends to report initiatives that were considered successful, suggesting publication bias. 15,16 There appear to be no trials to test whether cascading results in transfer of knowledge and skills to trainees, few attempts to compare it with other educational modalities, 15 and no initiatives where it has been combined with other approaches such as e-learning that are frequently employed in settings where direct access to continuing professional development (CPD) is limited.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Introduced in the 1940s, the cascade model is used to develop capacity in the commercial sector, 2 general education, 7 public health, 3,[8][9][10] and continuing medical education (CME). 11 Cost-effectiveness is assumed because small numbers of trained facilitators disseminate information to a wider population.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation